Racial Rift and the Rhetoric of Civic Nationalistic Ethos in Lee Kuan Yew’s Memoir - Bhusal, Mahendra (Pursuits: A Journal of English Studies, 2025)
Singapore’s former Prime Minister Lee Kuan Yew’s From Third World to the First: The Singapore Story 1965-2000, an internationally acclaimed political memoir, accounts his nation building narrative as he asserts that he had never seen a how-to-book for building a nation. This paper examines the way he narrates the story of managing the severe racial strife in Singapore during the initial phases of the nation being fermented in the1960s and 70s. He recounts the rhetoric of evoking the civic ethos in bolstering the civic nationalism and managing rooms for the multiple racial communities through the nation building discourse. Yew’s remarkable struggle to settle the racial rifts has been one of the dominant contents of his narration that reveals the sense of the exigencies of telling the story of the racial rift and its ultimate resolution by and large in giving shape to a harmonious multicultural nation of his dream. Taking the theory of civic nationalism evolved as early as from Rousseau’s The Social Contract (1762) to Hans Kohn’s notion of civic nationalism as the theoretical reference, the paper concludes that, by way of a broader nation building discourse, showcasing his conviction on civic nationalism, Yew’s narrative evokes the civic national ethos as a therapeutic remedy to heal the racial trauma as Singapore was taking the shape of a nation state.